The genus Sphaerocavum and the dominance of S. brasiliense and Microcystis wesenbergii (Microcystaceae, Cyanophyceae) in the algae bloom of Huacachina lagoon, Peru - Mendoza-Carbajal, Leonardo H. (2016)
The present work registers for the first time the cyanobacteria Sphaerocavum brasiliense Azevedo y Sant’Anna and Microcystis wesenbergii (Komárek) Komárek in Kondrateva (Microcystaceae, Cyanophyceae) in an algal bloom on Huacachina lagoon (Ica), including the first report of Sphaerocavum for Peru. We suggest the necessity of monitoring these bloom-forming cyanobacteria.